Partycypacja obywateli w rządzeniu. Problemy polskiej samorządności - Piróg, Tomasz; Masłyk, Tomasz (Wydawnictwa AGH, 2017)
This paper describes the issues related to the barriers of civic participation in local governments. It presents local governments as an institutional field, whose functioning does not depend solely on the decentralization of governance. In addition, the paper describes problems related to the functioning of Polish self-governments, whose broader description can be found in the articles collected in this volume.

Artykuł opisuje zagadnienia związane z barierami partycypacji obywatelskiej w samorządach terytorialnych. Przedstawiono w nim samorządy jako pola instytucjonalne, których funkcjonowanie nie zależy wyłącznie od ustaw decentralizujących rządzenie. Ponadto scharakteryzowano problemy związane z funkcjonowaniem polskich samorządów, których szerszy opis znalazł się w artykułach zgromadzonych w niniejszym tomie czasopisma.
Civil participation in governance. Problems of Polish self-government
Studia Humanistyczne AGH
Keywords: institutional field; local government; local democracy; pole instytucjonalne; samorząd terytorialny; demokracja lokalna